Stepwise design methodology and heterogeneous integration routine of air-cooled sic inverter for electric vehicle - Zeng, Zheng (2022)
Carrying on SiC devices, the air-cooled inverter of the electric vehicle (EV) can eliminate the traditional complicated liquid-cooling system in order to obtain a light and compact performance of the powertrain, which is considered as the trend of next-generation EV. However, the air-cooled SiC inverter lacks strategic design methodology and heterogeneous integration routine for critical components. In this article, a stepwise design methodology is proposed for the air-cooled SiC inverter in the power module, dc-link capacitor, and heat sink levels. In the power module level, an electrical-thermal-mechanical multiphysics model is proposed. The multidimension stress distribution principles in a six-in-one SiC power module are demonstrated. An improved power module is presented and confirmed by using the observed multiphysics design principles. In the dc-link capacitor level, ripple modeling of the inverter and capacitor are created. Considering the tradeoffs among ripple voltage, ripple current, and cost, optimal strategies to determine the material and minimize the capacitance of the dc-link capacitor are proposed. In the heat sink level, thermal resistance of air-cooled heat sink is modeled. Structure and material properties of the heat sink are optimally designed by using a comprehensive electro-thermal analysis. Based on the optimal design results, the prototypes of the customized SiC power module and heterogeneously integrated air-cooled inverter are fabricated. Experimental results are presented to demonstrate the feasibility of the designed and manufactured air-cooled SiC inverter.